As tensões entre liberdade e segurança no combate ao terrorismo: a situação das liberdades civis nos Estados Unidos da América pós 11 de setembro - Luísa Fernanda Turbino Torres (2016)
This research aims to understand the relationship between fundamental rights and national security using the post September 11 context in the United States, verifying how the measures taken by the Bush administration and the U.S. Congress intervened in the civil liberties of its citizens. For this purpose, it seeks to understand core concepts through a brief history of the Rule of law and civil liberties in the United States, from the colonial times to the twenty-first century. The study also explores other important concepts related to security, such as the U.S. homeland security and terrorism. Moreover, the research also analyze disruptions and continuities of Obama administration, adding prospects for the future of counter-terrorism. Finally, it seeks to comprehend the possible competition between freedom and security. The findings of this study show that both should be equally considered in the rule of law context and that the opposition in order to hierarchizes them is not gainful to fight terrorism.